Conceptual design of a web-based LNG plant management system through adoption of the integrated environment for design and maintenance - Kim, Joo-Dong; Choi, Shin-Beom; Lee, Jung-Min; Kim, Moon-Ki; Choi, Song-Chun; Hwang, In-Ju; Choi, Jae-Boong (Journal of mechanical science and technology, 2014)
The present paper aims to suggest a web-based LNG (Liquefied natural gas) plant management system that is applicable from the design stage through the operational lifetime of the plant. The usefulness of this program is maximized by combining a virtual plant and RAMS (Reliability, availability, maintainability and safety). To achieve this goal, principles related to a virtual plant and RAMS are reviewed and several modules were designed. In particular, the RBI (Risk based inspection) module based on the API (American Petroleum Institute) code was developed for implementing RAMS. To review the design and deliver geometrical information regarding the system and processes, several commercial softwares are chosen to develop the navigator module and virtual module of LPMS-RAMS (LNG Plant Management System based on RAMS). Also, several modules related to maintenance and safety, are developed. It means that the LPMS-RAMS has many applicable modules based on the concept of virtual plant and RAMS. Especially, The VR (Virtual reality) module in this system will be useful during the design stage for diverse types of LNG plants. Also, the RAMS module is expected to improve the efficiency and safety of the LNG plant during its operation.